New Data to the Rare Spider Species (Arachnida, Aranei) from Kyiv Region (Ukraine) - Yanul, V.; Terekhova, V.; Polchaninova, N. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
Seven rare spider species collected in the Kyiv Region are listed. Eresus moravicus Řezáč, 2008, Parasyrisca arrbonica Szinetár & Eichardt, 2009, and Enoplognatha bryjai Řezáč, 2016 are recorded for the first time from the East European Plain. P. arrbonica and E. bryjai are new to the spider fauna of Ukraine; Atypus muralis Bertkau, 1890, A. piceus (Sulzer, 1776), and Mustelicosa dimidiata (Thorell, 1875) are new the Kyiv Region. Comments on the geografical distribution and illustrations of four species are provided.